CLASSIFICATION OF ERRORS IN TRANSLATION OF LEGAL TEXTS FROM ENGLISH INTO RUSSIAN - YUGOVA, Maria (Comparative Legilinguistics, 2011)
The paper presents different classifications of translation errors made in translating texts from English into Russian. Special attention is given to psycholinguistic classifications based on exploring the mechanisms of speech mental processes engaged in the process of perceiving and generating texts in a foreign language. The paper emphasizes the psycholinguistic classification based on erratology, and gives its detailed description. In the given classification the translation errors are divided into errors of the expressive type and errors of the impressive type. The empiric part of the research includes the examples and analysis of errors that are very specific to the students’ translations of legal texts from English into Russian.